(untitled) (Journal of Pharmaceutical Negative Results, 2022)
umination and inhibition of the emotional style of university students is linked to gender and these emotions predispose to stressrelated diseases and are the cause of the negative effect they produce on personal and academic contact. Methods: In the present investigation, it was carried out considering a non-experimental design, it contains a population of 482 female and male university students. The instrument used was subjected to content validity through expert judgment and reliability was Kuder – Richardson (KR20), with a result of .960, considering high reliability and internal consistency. Results: The investigation concluded that female university students presented a 12% negative level, 29.7% presented a moderate level and 10.4% presented a positive level and male students 38.6% presented a negative level, 8.1% presents a moderate level and 1.2% presented a positive level of emotional style. Discussion: In relation to the results of the study, women have better levels of emotional style than men and coincidences with the background of this research are observed. Likewise, the importance of emotions being the relevant component to guarantee professional, personal and social competencies in the various contexts is established, and the management of emotions also guarantees in the process of using communication and management technologies. of time, the same ones that constitute a key for improvement. Finally, it has been important to identify gender differences in emotional style in order to recommend strategies to improve emotional style and rumination.